2005
DOI: 10.1016/j.matcom.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploding soliton and front solutions of the complex cubic–quintic Ginzburg–Landau equation

Abstract: We present a study of exploding soliton and front solutions of the complex cubic-quintic Ginzburg-Landau (CGLE) equation. We show that exploding fronts occur in a region of the parameter space close to that where exploding solitons exist. Explosions occur when eigenvalues in the linear stability analysis for the ground-state stationary solitons have positive real parts. We also study transition from exploding fronts to exploding solitons and observed extremely asymmetric soliton explosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…5) Different from the so-called "exploding solitons," found in numerical simulations [47,48] and experimentally confirmed in a passively mode-locked solid laser [49], our research indicates that the soliton amplification is continuous with the increase of z. The exploding solitons explode at a certain point, break down into multiple pieces, and subsequently recover their original shape [50]. However, in this paper, the soliton can be amplified continuously and stably, which can be confirmed by expanding the range of z (from 0 to 400, see Fig.…”
Section: Soliton Amplification Affected By the Gain Dispersioncontrasting
confidence: 57%
“…5) Different from the so-called "exploding solitons," found in numerical simulations [47,48] and experimentally confirmed in a passively mode-locked solid laser [49], our research indicates that the soliton amplification is continuous with the increase of z. The exploding solitons explode at a certain point, break down into multiple pieces, and subsequently recover their original shape [50]. However, in this paper, the soliton can be amplified continuously and stably, which can be confirmed by expanding the range of z (from 0 to 400, see Fig.…”
Section: Soliton Amplification Affected By the Gain Dispersioncontrasting
confidence: 57%
“…The following results contain two interesting features: pulsations and transitions between stable and unstable states. As it was explained in [43], a soliton with a very interesting pulsating behavior was discovered for a slightly asymmetric initial shape which is also Gaussian with amplitude A 0 = 5, and widths σ x = 0.8333 and σ y = 0.9091, see Fig. 3, for the set of parameters of row 2 of Table I.…”
Section: Ranges Of Parametersmentioning
confidence: 66%
“…9. As it has been shown in [43], this class may be unstable and leads to chaos. We also noticed that for the same set of parameters, the beams stop splitting and the soliton appears to be stable.…”
Section: Descriptionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this regime, a localized pulse circulating in the cavity experiences an abrupt structural collapse at certain points of its time evolution and subsequently recovers its original shape. Many numerical studies were reported in this framework [3][4][5][6][7][8][9]. Among the reported features is the stable existence of symmetric and asymmetric explosive localized states (LSs) over a wide range of parameters.…”
mentioning
confidence: 99%